Modeling and experimental verification of nonlinear behavior of cellulose nanocrystals reinforced poly(lactic acid) composites. (August 2019) - Shojaeiarani, Jamileh; Hosseini-Farid, Mohammad; Bajwa, Dilpreet
Highlights: A hyper-viscoelastic model was employed to study the mechanical response of poly (lactic acid). The material parameters were calibrated under tension-relaxation test data using finite element computational scheme. Drucker stability condition were evaluated for obtained constitutive constants. The reported material properties captured the short and long term viscoelasticity. Abstract: In this paper, a constitutive modeling framework was introduced to characterize the time-dependent behavior in poly(lactic acid) reinforced by cellulose nanocrystals (CNCs). The mechanical properties of PLA and its corresponding nanocomposites were analyzed at three different extension rates (1, 5, 10 mm/min) using a stress relaxation test. Six hyperelastic strain energy functions were employed to describe the instantaneous mechanical behavior. The deviatoric and volumetric material constants were verified using Drucker stability criterion, and the instability limits of each model were reported. Furthermore, a hyper-viscoelastic model consisting of Neo-Hookean strain energy function and time-dependent Prony series was used to study the viscoelastic behavior of PLA and the corresponding nanocomposites. The model constants were determined using finite element (FE) simulations through an iterative process for the whole loading history of the relaxation test. Nelder–Mead Simplex method was applied to optimize the results of the FE simulations using the experimental data. The mechanical response observed for PLA and nanocomposites from model exhibited a good agreement with both short and long-term experimental data, suggesting the applicability of the estimated material parameters by this technique. Graphical abstract: Image, graphical abstract